2013
DOI: 10.1111/nyas.12007
|View full text |Cite
|
Sign up to set email alerts
|

Addiction and corticotropin‐releasing hormone type 1 receptor antagonist medications

Abstract: Derangements in corticotropin-releasing hormone (CRH) through its type 1 receptor (CRHR1) have been identified in many pathologic conditions. Preclinical models of addiction find that small-molecule antagonists of CRHR1 can limit induction, maintenance, and relapse to drugs of abuse. Neuropsychiatric clinical trials of CRHR1 antagonists have shown mixed efficacy; treatment of addictive disorders has not been established, but finding effective treatments for addictive disorders is critical. Establishing effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 98 publications
(221 reference statements)
0
5
0
Order By: Relevance
“…Repeated stress exposure increases HPA axis dysregulation and can predict relapse in users of a variety of abused substances, including cocaine, alcohol, nicotine, and opiates, as well as in polysubstance abusers [ 18 21 ]. Over the past two decades, preclinical studies have demonstrated consistent effects of CRHR1 blockade on stress-mediated behavior, related neurochemistry, sympathetic nervous system activation, and neuroendocrine and immune function [ 34 ]. Further, variants in CRHR1 have been associated with depression [ 35 ], responses to antidepressants [ 36 ], and alcoholism [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Repeated stress exposure increases HPA axis dysregulation and can predict relapse in users of a variety of abused substances, including cocaine, alcohol, nicotine, and opiates, as well as in polysubstance abusers [ 18 21 ]. Over the past two decades, preclinical studies have demonstrated consistent effects of CRHR1 blockade on stress-mediated behavior, related neurochemistry, sympathetic nervous system activation, and neuroendocrine and immune function [ 34 ]. Further, variants in CRHR1 have been associated with depression [ 35 ], responses to antidepressants [ 36 ], and alcoholism [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…CRFR1 is the primary molecular site for stress activation. [ 6 ] CRFR1, a 415-amino acid protein, is the primary receptor subtype expressed in both brain and peripheral tissues. [ 7 ] In a genetically inactivated (CRFR1 −/− ) animal model, dopamine-mediated incentive behavioral manifestation of addiction, such as anxiety, is significantly increased.…”
Section: Introductionmentioning
confidence: 99%
“…Several methodological factors could have led to poor translation ( Pomrenze et al, 2017 ; Shaham and de Wit, 2016 ); if these are properly addressed, there could still be a path forward for these agents but, in all likelihood, therapeutic application may be narrower than originally hoped ( Spierling and Zorrilla, 2017 ). Alternative study designs may be needed that measure not only direct effects of the medication on substance use, but also intermediate stress-related phenotypes, e.g., coping or resilience ( Contoreggi et al, 2013 ). One potential moderating factor is that some clinical studies were conducted exclusively with female volunteers, which could influence the generalizability of findings.…”
Section: Neuropharmacological Targetsmentioning
confidence: 99%